Numerical Analysis of Liquid Immersion of Panels as a Cooling Technique. Issue 1 (April 2021) - Dixit, Krishna Kant; Saxena, Aditi; Yadav, Indresh
Abstract: The materials used in the manufacturing of solar panels is a semiconductor which is sensitive to the irradiation falling on it. The semiconductor materials begin to heat and becomes inefficient after certain point of temperature and the power output becomes too low to utilize. To overcome this problem of high temperature certain cooling techniques are implemented. The aim of this paper is to analyse the reduction in the temperature of the panels which can be obtained for different ambient conditions by implementing liquid immersion of panels as a cooling technique by simulating the equations involved in the dissipation and absorption of heat from the panels. The immersion of panels reduces the direct contact of panels with the heat absorbed from the irradiation by changing the refractive index of the medium from air to water.